Bark stripping by red deer was found in the vicinity of Budakeszi – a kind of game damage formerly received little attention - Tamás, Júlia; Ősi, Zsolt; Csontos, Péter (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
Intensive bark stripping by red deer was found in young forest stands near town Budakeszi, Hungary. Damaged trees were sampled in five 10 m by 10 m plots. In average, damaged zone started at 59 cm height and ended at 143 cm height from tree base. Considering tree and shrub species, debarking rate was the following: Fraxinus excelsior (89.3%), Euonymus europaeus (66.7%), Tilia platyphyllos (50.0%), Acer platanoides (40.0%) and Acer campestre (11.8%). In contrast, Acer pseudoplatanus, Cerasus avium, Crataegus monogyna and Quercus petraea trees remained untouched. Increasing human disturbance in the town's vicinity was discussed as a potential reason of the increased bark stripping activity of red deer.
Keywords: Cervus elaphus; Fraxinus excelsior; quantitative studies; bark stripping